(untitled) - Thrusfield, M. V. (London, 2007)
Veterinary Epidemiology is an invaluable reference source for veterinary general practitioners, government veterinarians, agricultural economists and members of other disciplines interested in animal disease. It will also be essential reading for undergraduate and intermediate-level
Keywords: Veterinary epidemiology,Bệnh dịch tể học